A Codebook-Adaptive Feedback Algorithm for Cellular-Based Positioning - Ting Jiang; Maozhong Song; Xuejian Zhao; Xu Liu (IEEE Access, 2018)
To ensure positioning accuracy and speed of cellular-based human position acquisition for location-based service in a smart system, channel state information between the base station (BS) and user equipment (UE) is required at the BS to acquire the location of users. In frequency division duplexing cellular systems, the most practical solution of channel state acquisition is that a downlink channel is quantized using a codebook and then fed back to the BS over the finite rate feedback channel. In this paper, an adaptive feedback algorithm based on codebook updating is proposed for cellular-based positioning. Different from traditional feedback schemes that the feedback codebook keeps constant during the transmission procedure, the codebook of the proposed algorithm is dynamically updated based on the varied channel by rearranging codewords synchronously at the BS and UE. The feedback overhead can be reduced effectively with low computation complexity during the feedback transmission. Numerical results validate the effectiveness of the proposed algorithm.